Sex education among adolescents in Latin America 2012 - 2021: a systematic review - Córdova-Chaccha, Gloria (2023)
Adequate sexual education in adolescents, support from family and educational institutions can help prevent unwanted pregnancies and sexually transmitted diseases. The objective of the study was to determine the number of existing publications on sexual education for adolescents in Latin America. The study was framed in a systematic review of publications in journals indexed in the Scielo and EBSCO databases, during the period between 2012 and 2021, following the PRISMA 2009 methodology. The results indicate that after applying the filters, 641 publications were identified in Scielo and 846.834 in EBSCO, making a total of 847.475 studies. Subsequently, applying the inclusion and exclusion criteria, and following the PRISMA methodology, 17 publications were selected as a sample. In this sense, the number of scientific articles developed on the subject has increased in recent years in a positive way. Likewise, Mexico is the country that has the highest number of publications. Likewise, the studies demonstrated a greater preference for the quantitative approach as opposed to the qualitative and mixed approach. Definitely, teaching in sexual health guarantees being prepared for life acting with autonomy and ethical principles.